The Relationship between Madrasah Head Leadership with the Teacher's Effectiveness in State MTs 2 Medan - M. Idrus Hasibuan; Nuraini Nuraini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to determine (1) How the implementation of madrasa head leadership in MTs Negeri 2 Medan, (2) How the effectiveness of teacher work in MTs Negeri 2 Medan, and (3) The relationship between madrasa head leadership with the effectiveness of teacher work in MTs Negeri 2 Medan . The hypothesis proposed in this study is: "There is a Positive and Significant Relationship between Madrasah Head Leadership and the Effectiveness of Teacher's Work in MTs Negeri 2 Medan." The study population was all teachers in MTs Negeri 2 Medan. To determine the sample size the total sampling technique was used and a sample of 79 teachers was obtained as research respondents. The method used in this research is quantitative research methods with descriptive statistical techniques. The instrument was designed in the form of a questionnaire for the madrasa head leadership variables and teacher work effectiveness. Data are analyzed through correlation techniques. The results of the analysis show that there is a relationship between the leadership of the madrasa head and the work effectiveness of MTs Negeri 2 Medan teachers by 0, 940 through the regression analysis of the madrasah headship leadership contributed significantly to the work effectiveness of MTs teachers. Negeri 2 Medan, namely 0.9402 x 100% = 88.36%. While the regression equation isÝ = 18.25 + 0.78X means that the higher the leadership of the madrasa head, the higher the work effectiveness of MTs Negeri 2 Medan teachers.